Nutritionist Guide to Direct-to-Consumer Genetic Tests and Precision Nutrition. Issue 5 (September 2019) - Dashti, Hassan S.; Tucker, Chandler
Abstract : Analogous to precision medicine, precision nutrition aims to tailor nutritional recommendations based on personal needs to optimize health. The field of nutritional genomics, which refers to the bidirectional interplay between dietary nutrients and the genome, is providing some of the necessary scientific evidence for precision nutrition. However, the extent of the clinical utility of nutritional genomics largely depends on the mode of disease/trait inheritance and remains unclear for prevalent, complex diseases, such as obesity, heart disease, and type 2 diabetes. Because genomic technology is now readily accessible through affordable personal DNA tests, it is now critical for nutritionists to establish a basic understanding in nutritional genomics to evaluate the validity of genetics-related "health claims" being provided by direct-to-consumer genetic testing companies. In this review, we provide examples of successful nutritional genomics studies, review current limitations, provide guidelines to evaluate health claims, and lastly discuss possible avenues and future outlooks for precision nutrition.